2018
DOI: 10.1111/asj.13082
|View full text |Cite
|
Sign up to set email alerts
|

Immune synergistic oligodeoxynucleotide from Lactobacillus rhamnosus GG enhances the immune response upon co‐stimulation by bacterial and fungal cell wall components

Abstract: Bacterial genomic DNA has recently been shown to elicit a highly evolved immune defense. This response can be selectively triggered for a wide range of therapeutic applications, including use as a vaccine adjuvant to immunotherapies for allergy, cancer, and infectious diseases. Previously, we identified a low-concentration immune synergistic oligodeoxynucleotide (iSN-ODN, named iSN34) from Lactobacillus rhamnosus GG that has immunosynergistic activity upon costimulation of target cells with ligands of Toll-lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Studies have confirmed that TLR1 to TLR9 all exist in IECs [130], but the exact mechanisms of TLRs underlying the regulation of intestinal homeostasis have yet to be fully illuminated. Bacterial cell walls lipoproteins, bacterial peptidoglycan, and fungal zymosan are recognized by TLR1, TLR2, and TLR6, respectively [131,132,133]. TLR4 is responsible for recognizing LPS produced by Gram-negative bacteria.…”
Section: Orchestrated Balance Between Mucosal Immune System and Gumentioning
confidence: 99%
“…Studies have confirmed that TLR1 to TLR9 all exist in IECs [130], but the exact mechanisms of TLRs underlying the regulation of intestinal homeostasis have yet to be fully illuminated. Bacterial cell walls lipoproteins, bacterial peptidoglycan, and fungal zymosan are recognized by TLR1, TLR2, and TLR6, respectively [131,132,133]. TLR4 is responsible for recognizing LPS produced by Gram-negative bacteria.…”
Section: Orchestrated Balance Between Mucosal Immune System and Gumentioning
confidence: 99%
“…The cells were subsequently incubated with different concentrations (2 × 10 6 and 2 × 10 7 CFU per well) of heat‐killed LIC37 (experimental) or LGG (control) for 2 hr before being stimulated with lipopolysaccharide (LPS, Sigma‐Aldrich) (100 ng/well) or with DMEM as a negative control. Intracellular levels of the transcripts encoding tumor necrosis factor (TNF)‐α, interleukin (IL)‐6, and IL‐10 and secretion of the corresponding proteins were assessed by real‐time quantitative PCR (RT‐qPCR) (Namai, Yamamoto, Sato, Ogita, & Shimosato, 2018; Nigar et al., 2018) and ELISA, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…In 2017, Nigar et al explored a novel ODN (named “iSN34”) incorporated into Lactobacillus rhamnosus , GGATCC53108, that has synergistic effects on the immune response in CpG-induced immune activation (47). The iSN34 sequence is TTCCTAAGCTTGAGGCCT (48). Originally, we evaluated inhibitory or suppressive ODN (iODNs) with a TTAGGG motif.…”
Section: Oligodeoxynucleotides As Immune Modulatorsmentioning
confidence: 99%
“…Thus, iSN34 may be an extraordinarily impressive adjuvant-mediated vaccine via Th1 that defends against intracellular pathogens, or iSN34 may provide antibody-mediated immunity compared to extracellular pathogens (47). We also conducted further investigations into the synergistic induction of IL-6 by the consolidation of iSN34 with the cell wall components of bacteria (TLR1/TLR2, TLR4) and fungi (TLR2/TLR6) (48). This review focuses on the synergistic immune effects of combining CpG ODNs with synthetic molecules associated with TLR ligands targeting inflammation and autoimmune diseases.…”
Section: Oligodeoxynucleotides As Immune Modulatorsmentioning
confidence: 99%
See 1 more Smart Citation